146k views
0 votes
Which expression is equivalent to -12(3x -3/4)?

User Orionss
by
5.6k points

2 Answers

6 votes

Answer:

- 36x + 9

Explanation:

- 12(3x -
(3)/(4) ) ← multiply each term in the parenthesis by - 12

= - 36x + 9

User MrTJ
by
5.8k points
2 votes

Answer:

-36x + 9

Explanation:

Given expression:


-12\left(3x-(3)/(4)\right)

Apply the distributive rule:


\implies -12 \cdot 3x -12 \cdot -(3)/(4)

Multiply -12 and 3x:


\implies -36x -12 \cdot -(3)/(4)

Apply the rule -a(-b) = ab:


\implies -36x +12 \cdot (3)/(4)

Convert 12 into a fraction:


\implies -36x +(12)/(1) \cdot (3)/(4)


\textsf{Apply the fraction rule} \quad (a)/(b) \cdot (c)/(d)=(ac)/(db)}:


\implies -36x +(36)/(4)

Divide the numbers:


\implies -36x +9

Therefore, the equivalent expression to the given expression is:

  • -36x + 9
User Gordon Henriksen
by
6.0k points